Maternal occupational pesticide exposure and risk of congenital heart defects in the national birth defects prevention study. Issue 10 (2nd June 2015) - Rocheleau, Carissa M.; Bertke, Stephen J.; Lawson, Christina C.; Romitti, Paul A.; Sanderson, Wayne T.; Malik, Sadia; Lupo, Philip J.; Desrosiers, Tania A.; Bell, Erin; Druschel, Charlotte; Correa, Adolfo; Reefhuis, Jennita; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Congenital heart defects (CHDs) are common birth defects, affecting approximately 1% of live births. Pesticide exposure has been suggested as an etiologic factor for CHDs, but previous results were inconsistent. METHODS We examined maternal occupational exposure to fungicides, insecticides, and herbicides for 3328 infants with CHDs and 2988 unaffected control infants of employed mothers using data for 1997 through 2002 births from the National Birth Defects Prevention Study, a population‐based multisite case‐control study. Potential pesticide exposure from 1 month before conception through the first trimester of pregnancy was assigned by an expert‐guided task‐exposure matrix and job history details self‐reported by mothers. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using multivariable logistic regression. RESULTS Maternal occupational exposure to pesticides was not associated with CHDs overall. In examining specific CHD subtypes compared with controls, some novel associations were observed with higher estimated pesticide exposure: insecticides only and secundum atrial septal defect (OR = 1.8; 95% CI, 1.3–2.7, 40 exposed cases); both insecticides and herbicides and hypoplastic left heart syndrome (OR = 5.1; 95% CI, 1.7–15.3, 4 exposed cases), as well as pulmonary valve stenosis (OR = 3.6; 95% CI, 1.3–10.1, 5 exposed cases); and insecticides, herbicides, and fungicides and tetralogy of Fallot (TOF) (OR = 2.2; 95% CI, 1.2–4.0, 13 exposed cases). CONCLUSION Broad pesticide exposure categories were not associated with CHDs overall, but examining specific CHD subtypes revealed some increased odds ratios. These results highlight the importance of examining specific CHDs separately. Because of multiple comparisons, additional work is needed to verify these associations. Birth Defects Research (Part A) 103:823–833, 2015. © 2014 Wiley Periodicals, Inc.